Gravitational field of the homogeneous rotational ellipsoidal body: a simple derivation and applications - POHÁNKA, Vladimír (Contributions to Geophysics and Geodesy, 2011)
We calculate the gravitational intensity and potential of a homogeneous body with the shape of the rotational ellipsoid. The calculation is performed in ellipsoidal coordinates and uses the properties of harmonic functions expressed as ellipsoidal harmonics. The resulting formulae for the internal and external fields are expressed in ellipsoidal coordinates and (in the case of external field) also in spherical coordinates. The results are used in the calculation of the gravitational field of a layered body whose layer boundaries are rotational ellipsoids with common centre and rotational axis; the density in each layer is constant. The equilibrium of such a layered rotating body is examined: it is found that there is no equilibrium for such a body except the case that the body is homogeneous (thus proving once more the important, but rarely mentioned, fact).